Penerapan Extreme Programming Pada Sistem Informasi Keuangan Sekolah Berbasis Website - Aditya Lapu Kalua (PT. SNN MEDIA TECH PRESS, 2022)
The results of interviews and observations conducted with schools every financial activity such as making budget plans, making financial reports, recording expenditure data in schools still uses the Microsoft Excel application. Based on these problems, a system is needed that can overcome problems in school financial recording using extreme programming methods. Extreme Programming (XP) is an approach or software development model that tries to simplify the various stages in the development process so that it becomes more adaptive and flexible. This goal is to produce a School Financial Information System with the Extreme Programming method. The overall result of technology acceptance model (TAM) testing for information system success amounted to 96.67% with criteria that are very good for the application of school financial information system design.